Pentingnya Keterbukaan Dan Akuntabilitas Dalam Mekanisme Judicial Review Di Mahkamah Agung - Palguna, I Dewa Gede; Shara, Made Cinthya Puspita (Acta Comitas, 2023)
The aims of this paper are to determine the procedural law in conducting judicial review by the Supreme Court of Indonesia and the application of the principles of openness and accountability. This article is prepared using the application of normative juridical research methods with a statutory approach, legal conceptual approach, and case approach. As the basis for the formulation of judicial authority or judicial review in the 1945 Constitution, it has illustrated that the Supreme Court of Indonesia has the right to carry out its duties as a judex jurist. MA RI there is also the Constitutional Court (MK) which has the authority to examine the law against the Indonesian Constitution. The results in this paper explain the regulation of the authority of the Supreme Court of Indonesia in carrying out its duties as a judex jurist, including the process of applying judicial review which refers to the application of the principles of openness and institutional accountability.